Step
*
1
1
1
1
1
2
1
of Lemma
evalall-sqequal
1. F : Base
2. F ~ λevalall,t. eval x = t in
                   if x is a pair then let a,b = x 
                                       in eval a' = evalall a in
                                          eval b' = evalall b in
                                            <a', b'> otherwise if x is inl then eval y = evalall outl(x) in
                                                                                inl y
                                                               else if x is inr then eval y = evalall outr(x) in
                                                                                     inr y 
                                                                    else x
3. j : ℤ
4. 0 < j
5. ∀x:Base. ((F^j - 1 ⊥ x)↓ 
⇒ ((fix(F) x)↓ ∧ (fix(F) x ~ x)))
6. x : Base
7. (F^j ⊥ (inl outl(x)))↓
8. (eval y = F^j - 1 ⊥ outl(x) in
    inl y)↓
9. 0 ≤ 0
10. x ~ inl outl(x)
⊢ (eval y = fix(F) outl(x) in inl y)↓ ∧ (eval y = fix(F) outl(x) in inl y ~ inl outl(x))
BY
{ (HasValueD (-3) THEN (FHyp 5 [-1] THENA Auto) THEN CallByValueReduce 0 THEN Auto) }
Latex:
Latex:
1.  F  :  Base
2.  F  \msim{}  \mlambda{}evalall,t.  eval  x  =  t  in
                                      if  x  is  a  pair  then  let  a,b  =  x 
                                                                              in  eval  a'  =  evalall  a  in
                                                                                    eval  b'  =  evalall  b  in
                                                                                        <a',  b'>  otherwise  if  x  is  inl  then  eval  y  =  evalall 
                                                                                                                                                                                  outl(x)  in
                                                                                                                                                                inl  y
                                                                                                                              else  if  x  is  inr
                                                                                                                                        eval  y  =  evalall  outr(x)  in
                                                                                                                                        inr  y 
                                                                                                                                        else  x
3.  j  :  \mBbbZ{}
4.  0  <  j
5.  \mforall{}x:Base.  ((F\^{}j  -  1  \mbot{}  x)\mdownarrow{}  {}\mRightarrow{}  ((fix(F)  x)\mdownarrow{}  \mwedge{}  (fix(F)  x  \msim{}  x)))
6.  x  :  Base
7.  (F\^{}j  \mbot{}  (inl  outl(x)))\mdownarrow{}
8.  (eval  y  =  F\^{}j  -  1  \mbot{}  outl(x)  in
        inl  y)\mdownarrow{}
9.  0  \mleq{}  0
10.  x  \msim{}  inl  outl(x)
\mvdash{}  (eval  y  =  fix(F)  outl(x)  in  inl  y)\mdownarrow{}  \mwedge{}  (eval  y  =  fix(F)  outl(x)  in  inl  y  \msim{}  inl  outl(x))
By
Latex:
(HasValueD  (-3)  THEN  (FHyp  5  [-1]  THENA  Auto)  THEN  CallByValueReduce  0  THEN  Auto)
Home
Index